2016
DOI: 10.1007/s11604-016-0545-3
|View full text |Cite
|
Sign up to set email alerts
|

A strategy to optimize radiation exposure for non-contrast head CT: comparison with the Japanese diagnostic reference levels

Abstract: We report the successful implementation of a new protocol with reduced radiation exposure for non-contrast head CT examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 2 publications
3
4
4
Order By: Relevance
“…A survey of CT dosage in Syria was conducted in 2009 and thus is relatively old with no updates available. Table 5 shows a comparison of the CTDI vol and DLP results with those of Australia (2015), ACR DIR (2016), Japan (2015), the EU (2014), Greece (2014), Egypt (2017), and ICRP (2007) [3,[16][17][18]. The values in this study were approximately lower than and comparable with those reported in other studies.…”
Section: Discussionsupporting
confidence: 77%
“…A survey of CT dosage in Syria was conducted in 2009 and thus is relatively old with no updates available. Table 5 shows a comparison of the CTDI vol and DLP results with those of Australia (2015), ACR DIR (2016), Japan (2015), the EU (2014), Greece (2014), Egypt (2017), and ICRP (2007) [3,[16][17][18]. The values in this study were approximately lower than and comparable with those reported in other studies.…”
Section: Discussionsupporting
confidence: 77%
“…The 3 rd quartile for CTDIvol and the effective dose values (Table 3) for the head imaging protocol (65.1 mGy, 2.83 mSv, respectively) were lower than the 3 rd quartile measured in some previous studies 19,34,35,37,39 , and higher than the 3 rd quartile measured in other studies 10,20,26,28,32,36,38,40,41,50, 52 . Similarly, the 3 rd quartile for CTDIvol and the effective dose values (Table 4) for the chest imaging protocol (16.6 mGy, 8.21 mSv, respectively) were lower than the 3 rd quartile measured in some previous studies 20, 23,35,50 , and higher than the 3 rd quartile measured in other studies 10,18,26,28-29,32,34,37-40, 52 .…”
Section: Discussioncontrasting
confidence: 50%
“…The 3 rd quartile for CTDIvol and the effective dose values (Table 3) for the head imaging protocol (65.1 mGy, 2.83 mSv, respectively) were lower than the 3 rd quartile measured in some previous studies 19,34,35,37,39 , and higher than the 3 rd quartile measured in other studies 10,20,26,28,32,36,38,40,41,50, 52 . Similarly, the 3 rd quartile for CTDIvol and the effective dose values (Table 4) for the chest imaging protocol (16.6 mGy, 8.21 mSv, respectively) were lower than the 3 rd quartile measured in some previous studies 20, 23,35,50 , and higher than the 3 rd quartile measured in other studies 10,18,26,28-29,32,34,37-40, 52 . Moreover, the 3 rd quartile for CTDIvol and the effective dose values (Table 5) for the abdomen-pelvis imaging protocol (17.9 mGy, 13.9 mSv, respectively) were lower than the 3 rd quartile measured in some previous studies 20, 23,34,35,41 , and higher than the 3rd quartile measured in other studies 10,18,26,28-29,31,32,36-40,50,51 .…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…In Japan, the latest diagnostic reference levels (DRLs) were published in 2015 [ 15 ] and do not yet reflect values obtained using SSDE. As such, a number of studies have explored the evaluation of SSDE [ 7 , 8 , 16 ]. In addition, many companies and public organizations have developed software programs for evaluating the organ dose and effective dose from CT examinations since the announcement of SSDE.…”
Section: Introductionmentioning
confidence: 99%